2007
DOI: 10.5737/1181912x1726671
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of husbands of women with breast cancer: Impact and response

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 21 publications
(17 reference statements)
1
22
0
2
Order By: Relevance
“…Other studies have examined the impact of breast cancer patients on family relationships. One study concluded that breast cancer can create tension in the lives of the partner and the demands of the family frequently outweigh the needs of the patient [11]. Semple and McCance [31] reviewed the literature, examining the impact on families when a parent is diagnosed with cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have examined the impact of breast cancer patients on family relationships. One study concluded that breast cancer can create tension in the lives of the partner and the demands of the family frequently outweigh the needs of the patient [11]. Semple and McCance [31] reviewed the literature, examining the impact on families when a parent is diagnosed with cancer.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in the months after a new diagnosis, these stressors include negotiating changes in occu- pational and family roles, interference with future life plans, and managing household and childcare responsibilities. [15][16][17][18] For couples dealing with advanced disease, cancer causes additional life stresses, such as declining functional abilities that bring about the necessity for couples to discuss how care and assistance with daily activities will be provided to the ill partner. 19,20 Couples also typically negotiate difficult choices regarding end-of-life treatments and care, cope with anticipatory grief regarding the loss of one's partner, manage child and family reactions, and talk about the ill partner's legacy in psychologic and practical matters.…”
mentioning
confidence: 99%
“…Men are also more likely to rely on informal supports (e.g. family and friends) for support [30,31,19].…”
Section: Introductionmentioning
confidence: 99%